QUALX2.0: a qualitative phase analysis software using the freely available database POW_COD. (1st April 2015) - Altomare, Angela; Corriero, Nicola; Cuocci, Corrado; Falcicchio, Aurelia; Moliterni, Anna; Rizzi, Rosanna
<x xml:space="preserve">Abstract</x> QUALX2.0 is the new version of QUALX, a computer program for qualitative phase analysis by powder diffraction data. The previous version of QUALX was able to carry out phase identification by querying the PDF‐2 commercial database. The main novelty of QUALX2.0 is the possibility of querying also a freely available database, POW_COD. POW_COD has been built up by starting from the structure information contained in the Crystallography Open Database (COD). The latter is a growing collection of diffraction data, freely downloadable from the web, corresponding to inorganic, metal–organic, organic and mineral structures. QUALX2.0 retains the main capabilities of the previous version: (a) automatically estimating and subtracting the background; (b) locating the experimental diffraction peaks; (c) searching the database for single‐phase pattern(s) best matching to the experimental powder diffraction data; (d) taking into account suitable restraints in the search; (e) performing a semi‐quantitative analysis; (f) enabling the change of default choices and strategies via a user‐friendly graphic interface. The advances of QUALX2.0 with respect to QUALX include (i) a wider variety of types of importable ASCII file containing the experimental diffraction pattern and (ii) new search–match options. The program, written in Fortran and C++, runs on PCs under the Windows operating system. The POW_COD database is exported in SQLite3 format.